"Reactive nanoprecipitation": a one-step route to functionalized polylactide-based nanoparticles. Issue 125 (1st December 2015) - Ficheux, Damien; Terrat, Céline; Verrier, Bernard; Gigmes, Didier; Trimaille, Thomas
Abstract : We report here a straightforward nanoprecipitation-based process to prepare functionalized polylactide (PLA) nanoparticles (NPs). Abstract : We report here a straightforward nanoprecipitation-based process to prepare functionalized polylactide (PLA) nanoparticles (NPs). It relies on an organic phase containing a PLA-based amphiphilic copolymer bearing N -succinimidyl esters that can spontaneously react with a peptide/protein located in the aqueous phase. The relevance of this strategy is supported by an improved antigenicity of immobilized HIV-1 Gag p24 protein.